UTILIZATION EOS PLATFORM AS CLOUD-BASED GIS TO ANALYZE VEGETATION GREENNESS IN CIREBON REGENCY, INDONESIA - Moh. Dede; Millary Agung Widiawaty (Journal of Information Technology and Its Utilization, 2020)
Cloud-Based GIS development has been increasing rapidly since the need for big computing for online spatial data. Besides Google Earth Engine, there is actually another Cloud-Based GIS with similar features namely EOS Platform. This study aims to determine the EOS Platform utilization as a Cloud-Based GIS to Analyze Vegetation Greenness in Cirebon Regency, Indonesia. The selection of research location based on the various phenomenon of development in the Cirebon Regency. Vegetation greenness analysis using the NDVI algorithm which available on EOS Processing and Landsat series images are obtained from Land Viewer. Changes in vegetation greenness were analyzed descriptively from NDVI values in two periods at each pixel in the same location. The results of the analysis with the EOS Platform show a decreasing vegetation greenness in the western and peri-urban areas caused by LULC changes. From this analysis, it is proven that EOS Platform can be used for effective and efficient satellite image processing. Even so, some EOS Platform products with BETA version status still show some obstacles related to integration between products.